Plankton Diversity as Mirrored by Silver Carp (Hypophthalmichthys molitrix) Gut Contents in Rupa Lake, Pokhara, Nepal - Ghising, Srishti (Nepalese Journal of Aquaculture and Fisheries, 2023)
A study was conducted in Rupa Lake from February to April of 2023 to investigate plankton diversity and gut content in silver carp (Hypophthalmichthys molitrix) in the lake. Samples were collected from 25 locations using a